Pedres (sílex),blau de Prússia i pintura de marcatge : revisant l’obra recent d’Òscar Padilla - Rovira, Jordi Morell i (2017)
This paper reviews the recent work of the artist/professor Òscar Padilla (1977). In his work, the artist uses repetitive materialswith the aim to enter into an imaginary related to the silicon and the history of technology. This recent work is not only relevant by the perceptual and physical qualities of its materials, but also by the concepts that the artist suggests, such as the panopticon and the control of time. Furthermore, his work brings us to some processes and concerns around the time of production in a sociocultural and hiperaccelerated context